AIR BUBBLE ENCAPSULATION OF EUKARYOTIC CELLS AND THERAPY FAILURES - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2023)
Background: The purpose of this manuscript is to introduce a newly discovered potential dangers of air bubbles used for therapeutic or diagnostic purposes into the human body. At present, the injection of air bubbles into the human body for diagnostic purpose is viewed positively by the medical/scientific community. In Vitro experiments are presented whereby cells isolation by air bubbles could interfere with chemotherapy treatments. Methods: Author’s own saliva sample was spitted out onto the center of a clean 25X75x1mm glass slide. The sample was placed and focused on the viewing platform of a video microscope. A toothpick was used to harvest inner cheek cells and gently transfer onto the spitted out sample. After focusing, areas were selected showing floating cells and air bubbles. Different laminar levels were observed by cells migrating at different levels. While microscopically observing the sample, the glass slide was disturbed by finger tapping, the aim to induce bubble bursting. Results: Deformed cells were observed when adhering to the outer surface of air bubbles. Additionally, undeformed cells seen at two distinct perpendicular layers when trapped within the floating bubbles. Noticed was a selective attraction of cells by the outer edge of the floating bubbles. Cells attached to the bubble’s edge were being deformed and attracted to each other. Cells were also observed passing unattracted when in a separate laminar flow under the floating bubble. The provocative tapping causing air bubbles to cavitate and burst. Conclusions: The bursting of an air bubble is not the only factor in floating eukaryotic cells deformation. In this manuscript video microscopy and still images are introduced demonstrating a newly found horizontal flat parallel energy field in the periphery of the oxygen bubble. This energy is evident in the free-floating air bubble interface as cheek eukaryotic cells adhere only to the flat round edge of a bubble. Cells are attracted, adhered to each other, and deformed by their own intrinsic attraction. Once the bubble bursts, cells and debris are dispersed, with cells adherence partially disturbed. Cell deformations persisting. It could be hypothesized that cancer cells trapped at different laminar layers inside the bubble be refractory to external chemotherapy agents thus retaining their cancer characteristics.